Preparation and properties of a new type of flexible epoxy resin based on a molecular network structure - X. F. Zhang; T. Cao; T. H. Zhao; C. Ma; P. Y. Liu (eXPRESS Polymer Letters)
In this paper, toluene-diisocyanate-trimer (TDI-T) was utilized to manufacture a new type of epoxy resin with high toughness via the co-polymerization method. In the procedure of preparing bisphenol A epoxy resin, before the reaction between bisphenol A (BPA) and epichlorohydrin (ECH), TDI-T was introduced to react with BPA for embedding flexible segments into the chain of epoxy resin, and obtaining the prepolymers, which are easy to form spatial interweaving network structures, then modified epoxy resin (TDI-T/EP) was manufactured. Mechanical properties, thermomechanical properties, and corrosion resistance of the cured TDI-T/EP were tested and characterized. Due to flexible segments and partial molecular network structure, the material presents high mechanical properties, especially the toughness, and the results show that the maximum tensile strength of cured TDI-T/EP reaches 30.3 MPa, and the maximum fracture elongation reaches 48.02%, at the same time the compressive strength arrives at 57.5 MPa. Compared with cured E-51, the toughness, strength, and fracture elongation are all strikingly enhanced. At the same time, the cured TDI-T/EP also has an excellent heat resistance and corrosion resistance, which avoided worries at home for its application. This work provides a new method for manufacturing high-toughness epoxy resins.